In search of the historicity of Indian Canon Law: The case of the Third Mexican Provincial Council - Traslosheros, Jorge E. (2021)
The study of the «Derecho indiano» has focused, mainly, on the instances of the different bodies of the secular power. However, to fully understand this legal tradition, it is also necessary to refer to the canon law, proper to the Catholic Church, which had a decisive influence on the conformation of the Colonial Hispanic America. Its discovery has followed his own dynamic, in which the study of the conciliar tradition of the different ecclesiastical provinces has been fundamental. In the present article we want to reconstruct the historiographical process that allowed us to discover the historicity of the Third Mexican Provincial Council, with emphasis on what happened between 1958 and 1987. Then the most important documentary findings were made and the questions that still guide our efforts were raised.